Teaching Through Content-Based and ESP Theories: Need for Vocational English in Agronomy and Veterinary Sections in Beni Secondary Schools. - Edmond, Kakule Kavulikirwa; Tembue , Zembele wa Ololo (Journal of Education and Practice, 2025)
Purpose: The study objective is to substantiate the effectiveness of teaching English through content-based and ESP theories in agricultural and veterinary options in Beni secondary schools. Methodology: In order to complete the research, the study used fieldwork for data collection. The collected information was subject to content analysis in order to understand what the respondents meant. Findings: The results reveal that English teachers teach more general English (72%) than vocational English (28%). Yet, agrovet pupils expressed the need to learn less general English (8%) than vocational English (92%). The materials in general English could not bring learners to comprehend, express, read, and know materials of their domains. Unique Contribution to Theory, Policy and Practice: Researchers tailored to pupils’ needs a syllabus containing texts of their fields. They made exercises to help teachers approach the texts. The proposed methodology is eclectic with much focus on visual aids. This implies that a change in content and pedagogy is likely to make agrovet pupils proficient in English and conduct their profession easily.